Cuban stingless bee livestock exhibit specialized floral resource use: a palynological study on honey samples from Matanzas and Mayabeque provinces - Fonte Carballo, Leydi; Rodríguez de la Cruz, David; Sánchez Sánchez, José; Sánchez Reyes, Estefanía; Lóriga Peña, Walberto; Demedio Lorenzo, Jorge; Díaz Solares, Maykelis; Morales Querol, Dariel (Sociobiology, 2022)
The knowledge of the different plant species that make up the feeding diet of animals is highly important to develop more efficient strategies. This research aimed to characterize the food potential available for the Cuban stingless bee livestock of the Matanzas and Mayabeque provinces. Palynological analysis was done using 60 g of pollen from sealed pots and 80 mL of honey from the ten randomly selected beehives (five in each province). The results showed that in the honey collected in Matanzas province, the most represented family was Amaranthaceae, followed by Myrtaceae and Fabaceae. Meanwhile, for Mayabeque, the most represented ones were the families Fabaceae and Myrtaceae. Regarding the stingless bee pollen of Matanzas provenance, the family Fabaceae prevailed, followed by Burseraceae and Myrtaceae. The pollen corresponding to Mayabeque coincided in showing Fabaceae as the most representative. In addition, pollen grains of small size (from 10 to 25 µm) were collected, with a marked representation of the pollen type of Mimosa pudica in the Mayabeque honey. It was concluded that the Cuban stingless bee livestock of the Matanzas and Mayabeque provinces had a specialist feeding behavior because a low number of plant taxa made up its diet.